Early and long term anamnestic response to HBV booster dose among fully vaccinated Egyptian children during infancy. Issue 15 (5th April 2018) - Salama, Iman I.; Sami, Samia M.; Said, Zeinab N.; Salama, Somaia I.; Rabah, Thanaa M.; Abdel-Latif, Ghada A.; Elmosalami, Dalia M.; Saleh, Rehan M.; Abdel Mohsin, Aida M.; Metwally, Ammal M.; Hassanin, Amal I.; Emam, Hanaa M.; et al.
Abstract: Objective: To evaluate early and long term anamnestic response to a booster dose of HBV vaccine among non-seroprotected children. Subjects and method: A national community based project was carried out on 3600 children aged 9 months to 16 years, fully vaccinated during infancy. They were recruited from 6 governorates representing Egypt. It revealed that 1535 children (42.8%) had non sero-protective anti-HBs (<10 IU/L) and were HBsAg or anti-HBc negative. A challenging dose of 10 μg of mono-valent Euvax HBV vaccine was given to 1121/1535 children. Quantitative assessment of anti-HBs was performed to detect early (2–4 weeks) and long term (one year) anamnestic responses. Results: Early anamnestic response developed among 967/1070 children (90.3%).Children having detectable anti-HBs (1–9 IU/L) significantly developed early anamnestic response (90%) compared to 85% with undetectable anti-HBs (<1 IU/L), P < 0.001. Multiple logistic analysis revealed that undetectable anti-HBs, living in rural residence and children aged 15–16 years were the most significant predicting risk factors for the absence of early anamnestic response (<10 IU/L), with AOR 2.7, 2.7 & 4.7 respectively. After one year, long term anamnestic response was absent among 15% of children who previously showed early response. Poor early anamnestic response and undetectable pre-booster anti-HBs were the significant predicting risk factors for absent long term anamnestic response, with AOR 18.7 & 2.7 respectively. Conclusion: Immunological memory for HBV vaccine outlasts the presence of anti- HBs and HBV vaccination program provides effective long term protection even in children showing waning or undetectable concentrations of anti-HBs. This signifies no need for a booster dose especially to healthy children.